The Relationship Between Liquidity, Leverage, Cash Flow, and Profitability On Financial Distress - Melfa Asi Gres Br Silalahi; Mukhzarudfa Mukhzarudfa; Dica Lady Silvera (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the relationship between liquidity, leverage, cash flow, and profitability and financial distress in property and real estate companies listed on the Indonesia Stock Exchange from 2021 to 2024. Financial distress is a condition in which a company experiences financial difficulties, characterized by insufficient operating cash flow to meet long-term and short-term obligations during the fall. Using signaling theory as a theoretical framework, this study employed purposive sampling and obtained a sample of 20 companies with 80 observations per company-year. Data were collected from secondary data sources, namely annual reports, and analyzed using correlation tests with Stata 17 software. The results indicate that liquidity has a high positive relationship with financial distress, leverage has a very high negative relationship with financial distress, cash flow has a low positive relationship with financial distress, and profitability does not show a significant relationship with financial distress